Sound Body, Present Time(s), Utopian Body, Immensity, Heterotopies and Other Voices (Urdimento: Revista de Estudos em Artes Cênicas, 2021)
Considering the continuous relations between the internal and external as well as the objective and subjective aspects of vocal creation, this article addresses the immensity of the poetic experience, Corpo Sonoro, Sound Body, in experimentation and theatrical composition laboratories, evoking a technique and plural dramaturgies between research practices and Foucault and Bachelardian notions about time(s), space(s) and the Body.
Keywords: Sound Body; Poetic Body; Utopian Body; Heterotopies; Voices